2019
DOI: 10.1001/jamanetworkopen.2018.6861
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Regular Exercise During Pregnancy on the Prevention of Postpartum Depression

Abstract: Key Points Question Does regular exercise during pregnancy prevent postpartum depression? Findings In this randomized clinical trial of 639 pregnant women, individuals allocated to receive the exercise program did not have significant reductions in postpartum depression. However, noncompliance with the intervention protocol was substantial and may have resulted in underestimation of the possible benefits of the treatment (as suggested by the instrumental va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
1
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(76 citation statements)
references
References 34 publications
1
63
1
11
Order By: Relevance
“…The majority of the reviewed studies found a negative association of PA with MH, and positive for physical inactivity studies. There are two studies [ 30 , 31 ] that found no association of PA with MH, and a third that found association with depression symptoms, but no association for patients with anxiety [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The majority of the reviewed studies found a negative association of PA with MH, and positive for physical inactivity studies. There are two studies [ 30 , 31 ] that found no association of PA with MH, and a third that found association with depression symptoms, but no association for patients with anxiety [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of the 27 studies included in this review, 14 (51.8%) were cross-sectional studies, 2 RCTs, and 11 follow-ups of a cohort. Different PA measures were assessed: 6 programmes of PA reporting an objective measure of PA [ 30 , 31 , 36 , 44 , 46 , 47 ], and the remaining 21 offering conclusions from studies based on self-reported PA. The included studies were critically assessed and their main focus was on finding an association of different types of PA with objective/clinically relevant symptoms for MH [ 31 , 39 , 41 , 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As both breastfeeding and physical activity are beneficial it would be reasonable to expect that mothers might want to do both [12]. There is some evidence for associations between physical activity during pregnancy and longer-term postpartum weight loss, lower rates of depression, improved quality of life, and longer breastfeeding [13,14,15]. Although there has been extensive research on the independent benefits of physical activity and breastfeeding for both mothers and infants, the association between these important issues has only rarely been studied [12,15].…”
Section: Introductionmentioning
confidence: 99%